Variability and inter-relationship among yield and quality parameters in bread wheat - Kant, Surya; Lamba, RAS; Panwar, I S; Arya, R K (Journal of Cereal Research, 2011)
The present study was carried out with the objectives of assessing the genetic variability, estimating the association between grain yield and its component traits and among themselves, which is essential to know the effectiveness of selection for simultaneous improvement in these traits. The material consisting of 42 diverse genotypes of bread wheat was grown in randomized block design with three replications in four environments created through manipulation of sowing dates during rabi season 2007-2008 at Hisar as well as Bawal locations. The grain yield per plant showed positive and significant correlation with effective tillers per plant, number of grains per ear, 1000 grain weight and biological yield per plant. However, it showed negative significant correlation with plant height in one or more environments. The path coefficient analysis revealed that biological yield per plant is the major contributor towards the grain yield per plant. Hence, main emphasis should be given on biological yield in breeding programme.